2016
DOI: 10.1007/s00592-016-0870-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerobic exercise intensity on glycemic control in type 2 diabetes: a meta-analysis of head-to-head randomized trials

Abstract: Although our meta-analysis had a limited sample size, increasing exercise intensity safely accentuated reductions in HbA1c in some people with type 2 diabetes. Different approaches have been used to increase exercise intensity (i.e., some used interval training, whereas others used higher-intensity continuous exercise). However, at this time, it is unclear which form, if any, leads to the most favorable results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
79
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 31 publications
9
79
1
2
Order By: Relevance
“…In contrast, basal and postexercise insulin-stimulated glucose uptake appears to be impaired and contribute to the development of chronic disease (8, 44, 45). Regular exercise in both healthy and clinical populations improves indices of glycemic control including glycated hemoglobin (HbA1c) and insulin sensitivity in a “dose”-dependent manner (duration and intensity) (2, 46). It is generally conceded that training-induced improvements in glycemic control lead to improved insulin action in part through the upregulation of key skeletal muscle glucose homeostasis regulatory proteins such as Akt1/2, AS160, AMPK, hexokinase 2, and importantly GLUT4 (6, 7).…”
Section: Exercise and Glycemic Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, basal and postexercise insulin-stimulated glucose uptake appears to be impaired and contribute to the development of chronic disease (8, 44, 45). Regular exercise in both healthy and clinical populations improves indices of glycemic control including glycated hemoglobin (HbA1c) and insulin sensitivity in a “dose”-dependent manner (duration and intensity) (2, 46). It is generally conceded that training-induced improvements in glycemic control lead to improved insulin action in part through the upregulation of key skeletal muscle glucose homeostasis regulatory proteins such as Akt1/2, AS160, AMPK, hexokinase 2, and importantly GLUT4 (6, 7).…”
Section: Exercise and Glycemic Controlmentioning
confidence: 99%
“…Regular exercise can assist in the prevention and management of metabolic disease (2). Even a single session of exercise can improve glycemic control for up to 48 h postexercise (35).…”
Section: Introductionmentioning
confidence: 99%
“…A number of reviews have also reported a positive impact of activity monitors on people with Type 2 diabetes . The additional information displayed on accelerometers, such as exercise intensity or estimated expended calories, may enhance the effect of some behaviour change techniques (such as goal setting or feedback on performance), increasing motivation and therefore physical activity . No systematic review, however, has specifically examined the effects of accelerometer use alone, or contrasted the impact of pedometers and accelerometers on physical activity behaviour within Type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to continuous moderate-intensity exercise (CMIE), high-intensity interval exercise (HIIE) has been shown to elicit comparable and/or greater improvements in glycemic control (Gibala et al, 2012; Liubaoerjijin et al, 2016). Notably, an improvement in glycemic control can be seen even after a single bout of exercise (Gillen et al, 2012; van Dijk et al, 2012; Little et al, 2014).…”
Section: Introductionmentioning
confidence: 99%